Re-Orientalism is on TV: From Salman Rushdie’s The Aliens Show to The Kumars at No. 42 - Mendes, Ana Cristina (2017)
Referring to postcolonial cultural production, Graham Huggan concludes that ‘the language of resistance is entangled, like it or not, in the language of commerce’ (Huggan 2001: 264). This chapter contends that Salman Rushdie’s work, being inextricably enmeshed in capitalist modes of cultural production, distribution, and exchange stands at the nexuses of representation and reconstruction, as well as of complicity and autonomy. This chapter draws connections between The Aliens Show, a situation comedy in Rushdie’s The Satanic Verses about a group of creatures from outer space, and The Kumars at No. 42, a BBC minority-based sitcom. Both Saladin, the co-star of the grotesque TV programme in Rushdie’s novel who plays the role of Maxim Alien, and Sanjeev Kumar, the protagonist of The Kumars at No. 42, are relentless in their shared ambition of becoming media personalities in Britain. In their pursuit of fame, Saladin, an Indian immigrant to London, constantly changes his hairstyle and clothes, while Sanjeev, a Br-Asian living in Wembley, has his family bulldoze the back garden to erect a state-of-the-art TV studio so that he can host his very own chat show. The key issue in these characters’ attempted assimilation to mainstream discourse is that they are equally aware of the provisionality of their cultural self-construction. Both texts highlight continuities and disruptions: from The Aliens Show’s focus on the misrepresentation of Otherness on the part of the media, mirroring the blatant ethnic stereotyping of the period from the 1960s to the 1980s, to the interstitiality of The Kumars at No. 42 which came to characterize Br-Asian TV comedy as from the late 1990s and early 2000s. What is interesting to note here are the dilemmas that result from the negotiation of Orientalist representations. Such representational dilemmas are framed in the context of a globalized world where transnational cultural industries simultaneously foster an expanded space for minority-based authorship and self-fashioning, and betray the unfeasibility of unmediated and unframed literary, cinematic, or other type of cultural self-representation.